IFPRI-Coordinated Research Project "Improving WTO Transparency: Shadow Domestic Support Notifications" - Nassar, Andre M.; Ures, Diego (2009)
Andre M. Nassar, Diego Ures 14th March-15th March 2008, International Food Policy Research Institute, Washington D.C.